Penggunaan Pewarna Alami pada Proses Anodizing terhadap Kekerasan Komponen Sepeda - Muhammad Abiyyu Raafi; Nani Mulyaningsih; Nila Nurlina (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The manufacturing industry continues to develop quality to improve productivity and business sustainability. One method commonly used in metal surface treatment is the anodizing process. One of these industries is the electroplating industry which uses chemicals as aluminum dyes that damage the environment. The purpose of this study is to determine the effect of using natural dyes turmeric, dragon fruit, and pandan leaves as coloring materials in the anodizing process of bicycle components on their hardness. The specimen used in this study is 1100 aluminum. The results showed that the highest hardness value using dragon fruit natural dye was 204.775 VHN.